Socialization of Regulations for Migrant Fishing Vessel Crew Protection to Palabuhanratu West Java Fisherman - Retno Muninggar; Akhmad Solihin; Julia Eka Astarini; Dahri Iskandar; Mustaruddin Mustaruddin; Thomas Nugroho (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2023)
The difficulty with capture fisheries operations is the lack of protection against the crew of fishing vessels, particularly those who work on foreign fishing ships. Uncertainty regarding compensation and working hours, the amount of unprocedural recruitments, a lack of proper pre-ship training, and other abuses of migrant rights are all common issues for migrant fisherman. Several fishermen from Palabuhanratu, West Java, who worked as crew members on migrant fishing vessels were unfamiliar with the different rules governing their rights and responsibilities while aboard foreign ships. To accomplish so, the regulations governing the protection of migrant fishing vessels must socialized. Keywords: migrant fishing vessel crew,Palabuhanratu, labor protection for migrant workers, fisherman